Materi Negara Hukum dan Hak Asasi Manusia dalam Pembelajaran di Sekolah Menengah - Jumiati, Jumiati (Jurnal Demokrasi, 2006)
This article tries to elaborate the matters of Rule of Law and Human Rights in learning process for the students of Secondary Schools in Indonesia. It is important that teachers and students understand these matters in order that they can participate in law enforcement at this country. Kata Kunci: Negara hukum, Hak Asasi Manusia, Konstitusi.